Chapter L'Adriatico, come sfondo - IVETIC, EGIDIO (Biblioteca di Studi Slavistici, 2019)
The author moves from the case of Gerasim Zelić to ponder on the concept of "Eastern Adriatic", which generally refers to a border area where different religions, political and administrative models, languages, cultures and identities come together. Assuming that the sea is a gigantic text through which the past can be read, the author presents the Eastern Adriatic as an example of mare storia and eventually suggests to apply the concept of "multiple borderlands" to this area, whose history is actually the history of numerous large and small boundaries that deserve a painstaking description.